Best evidence for improving function in children with cerebral palsy: Success is within reach. (23rd February 2022) - Jackman, Michelle; Sakzewski, Leanne; Morgan, Catherine; Boyd, Roslyn N.; Brennan, Sue E.; Langdon, Katherine; Toovey, Rachel A. M.; Greaves, Susan; Thorley, Megan; Novak, Iona
Abstract : This letter to the editor is on the Clinical Practice Guide by Jackman et al. on pages 536–549 of this issue.